Scaling up Local and Community Driven Development : A Real World Guide to Its Theory and Practice - Binswanger-Mkhize, Hans P.; de Regt, Jacomina P.; Spector, Stephen (World Bank, Washington, DC, 2017)
Local and Community Driven Development (LCDD) is an approach that gives control of development decisions and resources to community groups and representative local governments. Poor communities receive funds, decide on their use, plan and execute the chosen local projects, and monitor the provision of services that result from it. It improves not just incomes but people's empowerment and governance capacity, the lack of which is a form of poverty as well. LCDD operations have demonstrated effectiveness at delivering results and have received substantial support from the World Bank. Since the start of this decade, our lending for LCDD has averaged around US$2 billion per year. Through its support to local and community-driven programs, the Bank has financed services such as water supply and sanitation, health services, schools that are tailored to community needs and likely to be maintained and sustainable, nutrition programs for mothers and infants, the building of rural access roads, and support for livelihoods and micro enterprise. This eBook brings together the thoughts and experiences of many of the leading proponents and practitioners of LCDD, a phrase that evolved from Community-Driven Development, and most clearly describes the process of empowering communities and their local governments so they drive economic and social development upwards and outwards. This, too many, appears as a new paradigm, though it has actually evolved over the decades, since it emerged from India in the 1950s. While many LCDD projects have taken root, the key challenge now is how such islands of success, that is, the discrete LCDD projects, can be scaled up into sustainable national programs that build skills in decision-making, management, and governance.